2016
DOI: 10.1227/neu.0000000000001446
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablation of Newly Diagnosed Malignant Gliomas

Abstract: BBB, blood-brain barrierHGG, high-grade gliomaLITT, laser-interstitial thermal therapyWHO, World Health Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…Different methods of hyperthermia treatment for brain tumors are being actively investigated, including the use of magnetic nanoparticles [27,28] and laser for thermal ablation [29]. Our hyperthermia device avoids direct injury to the surrounding normal brain tissues which may be a problem when directly ablating the tumor with a laser.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods of hyperthermia treatment for brain tumors are being actively investigated, including the use of magnetic nanoparticles [27,28] and laser for thermal ablation [29]. Our hyperthermia device avoids direct injury to the surrounding normal brain tissues which may be a problem when directly ablating the tumor with a laser.…”
Section: Discussionmentioning
confidence: 99%
“…Although GBM is a diffusely infiltrative disease, gross total resection (GTR) is associated with increased progression-free survival and overall survival compared to subtotal resection (STR), which itself confers a survival benefit compared to biopsy alone [7]. Studies aiming to quantify a threshold extent of resection have concluded that a threshold at 78% resection of radiographic tumor is necessary to confer a survival benefit compared to radiation and chemotherapy alone [8][9][10][11]. Other recent studies have found an additional survival benefit from supra-total resection (i.e., resection beyond the contrast-enhancing tumor margins) to include any fluid-attenuated inversion recovery (FLAIR) abnormalities or a total right frontal or parietal lobectomy compared to GTR [12,13].…”
Section: Rationale For Use Of Litt For Glioblastomamentioning
confidence: 99%
“…Both systems have a computer workstation with software for MR thermal imaging analysis and control over laser treatment parameters [25]. The 1064 nm wavelength laser used in the NeuroBlate system allows for deeper tissue penetration and potentially larger ablation zone, while the Visualase 980 nm wavelength laser produces more efficient heating [9].…”
Section: Litt System Platformsmentioning
confidence: 99%
See 2 more Smart Citations